Maternal Hypertension as a Dominant Predictor of Neonatal Respiratory Distress Syndrome: A Cross-Sectional Study in a Regional Indonesian Hospital - Putu Ayu Prita Nandari Dewi; Putu Verita Wulandari (Open Access Indonesian Journal of Medical Reviews, 2025)
Neonatal respiratory distress syndrome (RDS) remains a significant cause of morbidity and mortality in newborns, particularly in developing countries. While prematurity is a primary risk factor, other maternal and neonatal factors, including maternal hypertension, contribute to its incidence. This study aimed to identify the risk factors for RDS in neonates treated at a regional hospital in Tabanan, Indonesia, with a particular focus on the role of maternal hypertension. A cross-sectional study was conducted using secondary data from medical records of neonates treated at Tabanan Regional General Hospital (RSUD) from January 2023 to December 2024. The study included neonates diagnosed with RDS and a control group without RDS. Data on maternal factors (hypertension, diabetes mellitus) and neonatal factors (gestational age, birth weight, gender, mode of delivery) were collected. Bivariate analysis using Chi-square and Fisher's exact tests was performed to determine associations, with a p-value <0.05 considered statistically significant. A total of 220 neonates were included in this investigation, with 114 (51.8%) diagnosed with RDS and 106 (48.2%) without RDS. Maternal hypertension was found to be significantly associated with an increased risk of neonatal RDS (p=0.021; OR=1.5, 95% CI 1.1-2.0). No significant associations were found between RDS and gestational age (p=0.056), birth weight (p=0.839), gender (p=0.689), mode of delivery (p=0.072), or maternal diabetes mellitus (p=0.248) in this study. In conclusion, maternal hypertension emerged as a dominant predictor of neonatal RDS in this regional Indonesian hospital setting. This finding underscores the importance of vigilant antenatal care and management of hypertensive disorders during pregnancy to potentially mitigate the risk of RDS in newborns.